The growth and jobs strategy and the reform of European cohesion policy. Fourth progress report on cohesion. COM(2006)281. + Annexes (Brussels, 2006)
"Regional Policy Commissioner Danuta Hübner has presented the Commission report on how the regions are performing in the 25 Member States plus Romania and Bulgaria, in relation to growth and employment. In this fourth progress report on cohesion it is noted that, on average, the least prosperous countries - the 13 with relatively lower GNI per head that are supported under the Cohesion Fund - reported 3.6 % growth over the period 1995-2005, considerably higher than the EU average of 2.2 % per year. The report also gives an overview of the trends regarding disparities among regions and of the preparations for the new cohesion policy 2007-2013."